New vision old challenges : the state of pre-primary education in Bangladesh - Nath, Samir R.; Ahmed, Kazi saleh; Chowdhury, A. M. Raza; ROY, Goutam; Rahman, M Habibur (Campaign for Popular Education, Bangladesh : European Union Delegation to Bangladesh, 2014)
A study report on pre-primary education in Bangladesh.